Gender Equality and Women’s Empowerment in Disaster Recovery - World Bank (World Bank, Washington, DC, 2020)
It is often assumed that all members of a population experience the impact of disasters in the same way. In the pre-disaster context, women’s and girls’ unequal access to social, political, and economic resources influences their access to post-disaster assistance and compensation for damage and losses. While the post-disaster context presents a host of challenges for women, it is important to recognize that women are not just victims of disasters. The strength of post-disaster recovery lies with how well it responds to the needs of both women and men. This guidance note aims to provide action-oriented guidance to local and national government officials and key decision makers who face post-disaster challenges and to assist them in incorporating gender-responsive recovery and reconstruction efforts across all sectors through robust gender assessments that lead to concrete needs identification and gender-specific recovery strategies and frameworks. Implementation of such actions will facilitate both a more resilient, sustainable recovery, and advances in reducing gender inequality. The note addresses the different challenges that women face in post-disaster recovery and reconstruction caused by underlying issues of inequality and marginalization. The note provides guidance on how to turn a post-disaster situation into an opportunity to enhance gender equality and women’s empowerment, with a focus on building back better, as the aftermath of a disaster can present opportunities for new and more progressive gender roles and relationships to emerge. The guidance note is structured around three key areas: identifying and prioritizing gender-specific recovery needs; protecting women and men from physical and psychosocial harm; and planning for gender-responsive recovery in the disaster recovery framework and empowering women for sustainable and resilient recovery. The final section of the paper provides a long-term outlook on strengthening gender responsive recovery systems.